2019
DOI: 10.1155/2019/3902828
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Free Vibration Analysis of Thin‐Walled Box Girder Considering Shear Lag Effect

Abstract: The thin-walled box girder (T-WBG) is widely applied in the long-span bridge structures during the past decades due to its lighter self-weight and better mechanical properties. The shear lag effect (SLE), an essential aspect of T-WBG which governs the stress and the deformation, is rather necessary to be revealed properly. The extraordinary issue of T-WBG analysis nowadays is the SLE impact on its dynamical response to external load. This paper proposes an improved finite element method (FEM) to obtain the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It should be noted that the dynamic responses of such footbridges are much more complicated and important than the static ones, especially when the static behaviour is pre-known. Luo et al [33] proposed a hybrid finite element method to study the dynamic characteristics of the thin-walled box girder by considering the SLE. It was found that the natural frequencies considering the SLE have a general descending trend.…”
Section: Studies On the Shear Lag Effect (Sle) And Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the dynamic responses of such footbridges are much more complicated and important than the static ones, especially when the static behaviour is pre-known. Luo et al [33] proposed a hybrid finite element method to study the dynamic characteristics of the thin-walled box girder by considering the SLE. It was found that the natural frequencies considering the SLE have a general descending trend.…”
Section: Studies On the Shear Lag Effect (Sle) And Research Gapsmentioning
confidence: 99%
“…The aforementioned studies [35][36][37][38][39] indicate that the natural frequencies of the structures might be reasonably altered due to the SLE. However, the existing studies [33][34][35][36][37][38][39] on the dynamic responses of thin-walled box girder considering the SLE were mainly focused on the natural vibration characteristics or free vibration responses. To the best knowledge of the authors, however, there are very few studies related to SLE focusing on the forced vibrations of thin-walled box girder, not to mention the corresponding vibration control measures.…”
Section: Studies On the Shear Lag Effect (Sle) And Research Gapsmentioning
confidence: 99%